The Impact of Value-based Leadership on Faculty’s Intrinsic Work Motivation in China: the Mediation of Teacher Efficacy - Zhao, Xiangge; Wong, Chee Hoo (INTI International University, 2022)
This study tested the impact of value-based leadership on Chinese faculty’s intrinsic work motivation and examined the mediating effect of teacher efficacy in the relationship. Data was collected from a sample of 84 faculty members from different universities in China and SmartPLS was used in the data analysis. The findings indicated that value-based leadership had significantly positive impact on faculty’s intrinsic work motivation, and teacher efficacy partially mediated the relationship between value-based leadership and intrinsic work motivation. The findings can facilitate the understanding of how to increase faculty’s intrinsic work motivation at the universities in China.